The Role of Purchase Intention, Content Quality with Artificial Intelligence (AI) and Brand Awereness in Increasing Tokopedia’s Market Share - Bharata, Andhi; Prihandoko, Danang; Ramadhani, Rani (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Rapid advancements in digital technology have fundamentally transformed customer behavior, particularly within the e-commerce industry. Tokopedia remains one of the major online marketplaces in Indonesia; however, its market share has experienced pressure due to increasing competition from platforms such as Shopee and TikTok Shop. In response to this dynamic landscape, this study aims to analyze how Content Quality enriched with artificial intelligence (AI) elements influences Tokopedia’s market share, with a specific focus on three key determinants: purchase intention, content quality, and brand awareness. A quantitative research approach was employed through an online survey distributed to active Tokopedia users. A structured questionnaire was administered to 100 respondents residing in Jakarta, and the collected data were analyzed using IBM SPSS Statistics 23. The findings reveal that all three independent variables exert a positive and significant effect on Tokopedia’s market share. These results highlight the strategic importance of AI-driven features—such as personalized recommendations, automated content optimization, and user-adaptive interfaces—in strengthening customer engagement. Enhanced content quality supported by AI not only improves user experience but also contributes to the development of stronger brand awareness, which subsequently drives higher purchase intentions. Overall, the study underscores the necessity for Tokopedia to continuously refine its AI-based content strategies to remain competitive in the rapidly evolving digital marketplace. Strengthening AI integration is expected to help Tokopedia maintain relevance, elevate customer satisfaction, and secure a more sustainable market position amid increasingly aggressive competition.